2020
DOI: 10.1186/s13045-020-00855-9
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of mantle cell lymphoma in Asia: a consensus paper from the Asian Lymphoma Study Group

Abstract: Background: Mantle cell lymphoma (MCL) is a B cell malignancy that can be aggressive and with a poor prognosis; the clinical course is heterogeneous. The epidemiology of MCL in Asia is not well documented but appears to comprise 2-6% of all lymphoma cases based on available data, with variation observed between countries. Although international guidelines are available for the treatment of MCL, there is a lack of published data or guidance on the clinical characteristics and management of MCL in patient popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 77 publications
(108 reference statements)
0
32
1
1
Order By: Relevance
“…Another explanation is that our patients tolerated better the ibrutinib treatment, which resulted in a longer duration of treatment (Table 1). Based on the favorable outcomes, a recent consensus guideline recommended the use of ibrutinib in the second-line rather than later-line setting [9]. Compared to previous studies [10], the post-ibrutinib OS was more favorable in the present study at 19.4 months (vs. 5.8 months).…”
contrasting
confidence: 54%
“…Another explanation is that our patients tolerated better the ibrutinib treatment, which resulted in a longer duration of treatment (Table 1). Based on the favorable outcomes, a recent consensus guideline recommended the use of ibrutinib in the second-line rather than later-line setting [9]. Compared to previous studies [10], the post-ibrutinib OS was more favorable in the present study at 19.4 months (vs. 5.8 months).…”
contrasting
confidence: 54%
“…Variants with a low frequency of SOX11 negativity and IGHV-mutated genes are more indolent and associated with better prognosis. It is useful to confirm SOX11 negativity with hypermutated IGHV to identify a clearly indolent disease [ 54 , 55 ]. Sílvia et al demonstrated that SOX11 knockdown reduced engrafted tumor growth in vivo, which is consistent with the indolent clinical course of human SOX11-negative MCL [ 38 ].…”
Section: The Expression Level Of Sox11mentioning
confidence: 99%
“…In recent years, some cases of MCL have been characterized by IGHV mutations, and they are truly associated with an indolent disease course [ 57 , 59 ]. The typical clinical presentation of patients with IGHV mutations comprises leukemic non-nodal CLL-like, including splenomegaly, a Ki-67 proliferation fraction < 10%, a low tumor burden and noncomplex karyotypes [ 55 ]. The identified VH rearrangements in indolent MCL were VH1, VH2, VH3 and VH4 [ 3 ].…”
Section: Ighv Mutationsmentioning
confidence: 99%
“…Most recently, the advent of Bruton’s tyrosine kinase (BTK) inhibitors represented a breakthrough in the treatment of B-cell NHL and has proven beneficial in clinical trials on MCL [ 11 , 12 ]. A recent consensus paper by the Asian Lymphoma Study Group has also recommended the use of BTK inhibitors for R/R MCL [ 13 ]. However, treatment outcomes with each subsequent line of therapy, especially involving the use of novel-therapies, remain poorly characterized.…”
Section: Introductionmentioning
confidence: 99%